High Serum Ratio of Soluble Fms-Like Tyrosine Kinase 1 (sFlt-1) to Placental Growth Factor (PIGF) and High Level of Low-Density Lipoprotein (LDL) as Risk Factors of Preeclampsia - A.A.N. Jaya Kusuma; Endang Sri Widiyanti; I Wayan Megadhana; Putu Doster Mahayasa; Ryan Saktika Mulyana; Kevin Agastya Duarsa (Syntax Corporation Indonesia, 2023)
Preeclampsia is an obstetric disease that is a health problem worldwide, including in Indonesia. Several studies have shown that changes in the maternal spiral arteries are thought to lead to preeclampsia. Preeclampsia in this decade has been associated with changes in angiogenesis regulatory proteins originating from the placenta and circulating in the mother's blood circulation, namely soluble FMS-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF). The author was interested in examining the ratio of sFlt-1/PIGF and low-density lipoprotein (LDL) to the incidence of preeclampsia in pregnant women. This study used a case control analytic observational design. The research sample was selected by consecutive sampling of 20 cases and 20 controls. Univariate analysis was used to describe patient characteristics descriptively, and bivariate analysis was used to determine the relationship between the 2 variables There is no significant difference in the characteristics of the research subjects. Low PIGF levels are a risk factor for preeclampsia (OR 4.33; p 0.0302) with a cut-off value of 24.5. High sFlt-1 levels are a risk factor for preeclampsia (OR 4.33; p 0.027) with a cut-off value of 869.5. A high sFlt-1/PIGF ratio is a risk factor for preeclampsia (OR 4.33 p 0.030) with a cut-off value of 38. High LDL levels are a risk factor for preeclampsia (OR 6.0; p 0.013) with a cut-off value of 150 ,2. Low placental growth factor (PIGF), high levels of soluble FMS-like tyrosine kinase 1 (sFlt-1), and high levels of LDL are risk factors of preeclampsia in pregnant women.